EFEKTIVITAS MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUALY) DALAM MENULIS TEKS DRAMA PADA SISWA KELAS VIII - Tamba, Losten; Liana, Liana; Hasibuan, Asnita; Sidabutar, Yuni Rosmasari (Pendidikan Bahasa Indonesia dan Sastra (PENDISTRA), 2023)
This research aims to determine (1) the differences in students' writing of drama texts before and after using the SAVI learning model, and (2) the effectiveness of using the SAVI learning model in writing drama texts for class VIII students at Free Methodist Middle School-1 Medan. This research design uses quantitative research using an experiment, namely a pre-experimental design with a one-group pretest-posttest design type. The data analysis techniques used are normality test, homogeneity test and Paired T-Test. The results of the research showed that there was a significant difference in students' ability to write drama texts before and after being given treatment. It can be seen from the average score before being given treatment, namely 16.86 and the average score after being given treatment, namely 24.06. The results of this research also prove that learning to write drama texts using the SAVI learning model has proven to be effective. The effectiveness can be seen from the results of the Paired T-Test which produces a value (t count: 12.408>t table: 2.030), and a P value of 0.000 (0.000<0.05) at the 5% significance level. Keywords: effectiveness, SAVI learning model, writing drama texts, junior high school students